Microstructural characteristics and mechanical behavior of B4Cp/6061Al composites synthesized at different hot-pressing temperatures. Issue 8 (August 2019) - Gao, Minqiang; Chen, Zongning; Kang, Huijun; Guo, Enyu; Li, Rengeng; Fu, Ying; Xie, Honglan; Wang, Tongmin
Abstract: B4 Cp/6061Al composites have become important structural and functional materials and can be fabricated by powder metallurgy and subsequent hot rolling. In this work, the effects of the hot-pressing temperature on microstructures and mechanical behaviors of the B4 Cp/6061Al composites were investigated. The results showed that compared with the T4 heat treated B4 Cp/6061Al composite hot pressed at 560 °C, the yield strength and failure strain of the composites hot pressed at 580 °C were increased to 235 MPa and 18.4%, respectively. This was associated with the interface bonding strength between the B4 C particles and the matrix. However, the reaction products, identified to be MgAl2 O4 phases, were detected in the composites hot pressed at 600 °C. The formation of the MgAl2 O4 phases resulted in the Mg depletion, thus reducing the yield strength to 203.5 MPa after the T4 heat treatment due to the effect of the solid solution strengthening being weakened. In addition, the variation of hardness and electrical conductivity was mainly related to the Mg content in the matrix. Based on the as-rolled microstructures observed by SEM, SR-μCT and fracture surfaces, the deformation schematic diagram was depicted to reflect the tensile deformation process of the composites.